Nutrient dynamics in restored and unrestored urban streams in the Piedmont ecoregion of South Carolina - Jordan, Emily N.; Sahoo, Debabrata; Sawyer, Calvin B.; Pike, Jeremy W.; Park, Dara M.; White, Sarah A.; Haggard, Brian E. (Frontiers in Environmental Science, 2025)
The United States invests billions of dollars annually to perform stream restoration projects, yet few studies have investigated the effects this ecosystem manipulation has on nutrient cycling and associated water quality. Water quality improvement remains a substantial motivation for mitigating catchment-scale disturbances, especially in urban streams. Various urban land use practices impact the transfer and transport of nutrients such as soluble reactive phosphorus, ammonium, and nitrate plus nitrite from land into the streams and rivers. The uptake length (Sw), or the distance a dissolved nutrient travels downstream within a stream reach, can be measured using short-term nutrient injections, where shorter uptake lengths suggest greater nutrient retention. This study evaluated the efficacy of using nutrient injection experiments as a monitoring tool to assess nutrient retention efficiency in first-order urban restored (RES) and urban unrestored (URE) stream reaches within the Piedmont ecoregion of South Carolina during the winter and summer seasons of 2022. Results suggested that the lack of fine sediment, such as silt and clay, may affect the nutrient cycling of phosphorus. The total nitrogen:total phosphorus ratio indicated the stream was phosphorus-limited during the experiments. The mean soluble reactive phosphorus uptake length throughout the study was shorter in RES than URE, suggesting that the restored reach was more efficient in retaining dissolved phosphorus. During summer injection, RES observed the shortest soluble reactive phosphorus uptake length of 77 m, while URE marked the longest uptake length of 3059 m during the same period. However, during winter injections, the URE segment had both the shortest and longest uptake lengths. In summer, RES exhibited noticeably shorter ammonium uptake lengths, while ammonium uptake lengths could not be calculated in URE. The presence of engineered pools in RES assisted in nutrient dynamics and helped trap nutrients, particularly soluble reactive phosphorus and ammonium, and could be prioritized in stream restoration efforts. Preliminary results from this study could provide helpful insights into the effectiveness of stream restoration and in-stream structures on nutrient dynamics, although further research is needed.